Improving the WHO Surgical Safety Checklist sign-out. Issue 3 (7th May 2021) - Tully, P A; Ng, B; McGagh, D; Meehan, N; Khachane, A; Higgs, J; Newman, M; Morgan, L; David, E; McCulloch, P
Abstract: Background: The WHO Surgical Safety Checklist has been shown to reduce perioperative morbidity and mortality worldwide. There is evidence to suggest that sign-out is the most poorly performed phase of the checklist as it coincides with a period of high workload for team members. This study aimed to see whether modification of this process might result in greater compliance. Methods: A controlled longitudinal (before and after) study was performed to evaluate the effect of a modified checklist sign-out on compliance in a single surgical department. Checklist quality was evaluated by measurement of checklist completion, active participation, and team member presence. Workload assessment was performed to identify the optimal moment for the sign-out process. The sign-out process was modified through an iterative multidisciplinary approach, informed by results from the workload assessment. Feedback was obtained through staff surveys. Results: A total of 185 operations were used, with an intervention group in vascular surgery and a control group in orthopaedics. The optimal timing for sign-out was identified as after final wound closure. The modified sign-out process improved active participation of team members (21 of 34 versus 31 of 34; P  = 0.010). In the control group, complete compliance improved (48 of 76 versus 30 of 41; P  = 0.041). However, active participation decreased (53 of 76 versus 19 of 41; P  = 0.022). No differences were noted between groups in team member presence. Eighteen of 21 staff questioned viewed the modifications positively. Conclusion: The optimal sign-out timing was identified as immediately after final wound closure prior to undraping the patient. Abstract : In an analysis using a workload-based approach, it was found that the optimal WHO checklist sign-out timing was during final wound closure. This finding was used to reiteratively modify the WHO checklist sign-out process, leading to improved active participation between team members.